Festival and events management : (Routledge, 2004)
Festivals, events and the cultural experience; Managing the arts, culture and leisure experience; Marketing, revenue and retail operations; Policies and strategies of art and leisure event management; ase studies and contemporary issues of arts and leisure festivals and events.